2020
DOI: 10.3390/s20205777
|View full text |Cite
|
Sign up to set email alerts
|

Study of Three Interface Pressure Measurement Systems Used in the Treatment of Venous Disease

Abstract: The aim of the publication is to report the accuracy, repeatability and the linearity of three commercially available interface pressure measurement systems employed in the treatment of venous disease. The advances in the treatment and management of chronic venous disease by compression therapy have led to considerable research interest in interface pressure measurement systems capable of measuring low-pressure ranges (10–60 mmHg). The application of a graduated pressure profile is key for the treatment of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Valentim et al used Flexiforce to measure the force exerted by the tongue and upper lip on the teeth of 28 subjects during rest and swallowing and found that the lips exerted more force on the upper central incisor than the tongue does at rest, while during swallowing, there was no difference between the force of the tongue and the lips on the teeth (Valentim et al, 2014). However, some scientists have shown that these sensors are not as accurate as other types of pressure sensors (Athavale et al, 2020;Nandasiri et al, 2020).…”
Section: Piezoresistive Transducermentioning
confidence: 99%
“…Valentim et al used Flexiforce to measure the force exerted by the tongue and upper lip on the teeth of 28 subjects during rest and swallowing and found that the lips exerted more force on the upper central incisor than the tongue does at rest, while during swallowing, there was no difference between the force of the tongue and the lips on the teeth (Valentim et al, 2014). However, some scientists have shown that these sensors are not as accurate as other types of pressure sensors (Athavale et al, 2020;Nandasiri et al, 2020).…”
Section: Piezoresistive Transducermentioning
confidence: 99%
“…It also demonstrated a lower SD and consistency with a subsurface (mimicking subcutaneous) pressure exertion when compared with an electrical-based (piezoresistive) sensor 32,33 . Other researchers verified that the PicoPress and AMI air-pack sensors are more accurate than the FlexiForce (piezoresistive sensor) in an examination with a manometer 34 . Further, PicoPress is recommended for in vitro study of compression bandages, and training programs for clinical practitioners are available 7,35 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Other researchers verified that the PicoPress and AMI air-pack sensors are more accurate than the FlexiForce (piezoresistive sensor) in an examination with a manometer. 34 Further, PicoPress is recommended for in vitro study of compression bandages, and training programs for clinical practitioners are available. 7,35 However, the PicoPress and Kikuhime might be inaccurate when compared with computationally calculated pressures.…”
Section: Conventional Pressure-measuring Devicesmentioning
confidence: 99%
“…Given: (1) the smaller limits of agreement and slope parameter noted above; (2) that the differences measured in the current study were > 3 mmHg; and (3) that all pressure measurements were made along the posterior aspect of the leg as recommended by [39]; it can be concluded that the Kikuhime pressure monitoring device was adequate for making the measurements here. Another recent study [41] noted that the dimensions of the air-filled sensor on a pressure monitoring device may influence the accuracy of the pressure measurement, and the PicoPress has a relatively large sensor area (50 mm) which may limit its ability to measure pressure accurately on small or curved areas. Conversely, the Kikuhime device has a smaller sensor area (38 × 30 mm) which makes it more suitable for measuring pressure on areas with high curvatures that are found on parts of the human leg (e.g.…”
Section: Discussionmentioning
confidence: 99%